Neue Allergene für die Berufsdermatologie? - Mahler, Vera (Hautarzt, 2021)
Background: The environment is continuously subject to change. Exposures in the work environment and therefore the importance of occupational type I and type IV allergens may change. Objectives: The most important trends concerning occupational allergens, new occupational allergens/allergen exposures, the diagnostic procedure to detect new allergens in practice and regulatory developments are presented. Materials and methods: Building on known relevant allergen exposures in occupational dermatology, published trends from clinical cohorts are evaluated and a systematic literature search (PubMed 2016–2021) for new occupational allergens is also performed Results: Occupations with the highest incidence of occupational allergic contact urticaria and/or protein contact dermatitis include bakers, farmers and farm workers, veterinary technicians, veterinarians, cooks, dairy and livestock workers, gardeners, and hairdressers. The highest risk of developing occupational contact dermatitis is in health care, agriculture, metalworking occupations and machine operators, the food sector, service industries, and construction occupations. The search strategy “new occupational allerg*” yielded 603 hits and “novel occupational allerg*” 158 hits. A total of 25 papers included results relevant to the research question and were processed. New protein-based immediate-type allergens, as well as contact allergens (haptens) relevant for occupational dermatology, are presented. Conclusions: Current trends on known occupational allergens and new occupational allergens in the period 2016–2021 can be identified. Only a thorough individual workplace history and testing of patients’ own materials can identify new allergens in occupational dermatology.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Allergic contact dermatitis; Contact urticaria; Occupational allergy; Protein contact dermatitis; Workplace environment